The Success of Local Contractors in The Procurement of Construction Projects in Kendari, South East Sulawesi, Indonesia - M. Akbar Kurdin; La Welendo; Rifa’i Maulana (Institut Teknologi Sepuluh Nopember, 2017)
This study aims to identify the diverse formulation of the problem related to the success of winning the construction project procurement for local construction company in Kendari. The urgency of this study is to answer the factors that determine the success of local contractors in the construction project procurement process in Kendari. The method used in this study is a statistical analysis method. Dimensions are used to measure success in the procurement of construction projects in this research is the company's experience, equipment and tools, human resources, process control, reputation / achievement contractors, financial, project organization, workplace safety. Dimensions is formulated into 22 variables to be measured. From the findings of research on the variables that influence the success of winning the procurement of construction project in Kendari obtained linear regression models, namelyY = -0,401 + 0,448 X2 + 0,576X14 + 0,273X12. The analysis results obtained from the dominant factors that influence the success of winning the construction procurement namely a kind of work that have been done, the project owner relationship with the contractor, and the methods and strategy implementation and control of the work to be done.